Influence of Corporate Governance on Financial Performance of Listed Firms in Germany - Fischer, Mia (International Journal of Finance, 2025)
Purpose: The purpose of this article was to analyze influence of corporate governance on financial performance of listed firms in Germany. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Research on German listed firms shows mixed results regarding corporate governance’s impact on financial performance. While strong governance structures enhance firm performance, mere compliance with governance codes does not guarantee financial benefits. Capital structure also influences this relationship, suggesting that governance effectiveness depends on firm-specific factors and economic conditions. Unique Contribution to Theory, Practice and Policy: Agency theory, stewardship theory & resource dependence theory may be used to anchor future studies on the influence of corporate governance on financial performance of listed firms in Germany. Listed firms should strengthen board independence by ensuring an optimal board composition with diverse skills, expertise, and gender representation to enhance strategic decision-making. Regulatory agencies should strengthen corporate governance compliance frameworks by enforcing stricter disclosure requirements and board accountability measures for listed firms.